Lemnicola hungarica (Bacillariophyceae) and the new monoraphid diatom Lemnicola uniseriata sp. nov. (Bacillariophyceae) from South Korea. Issue 1 (2nd January 2018) - Shi, Yan; Wang, Pengbin; Kim, Ha-Kyung; Lee, Hyuk; Han, Myung-Soo; Kim, Baik-Ho
Abstract : Many achnanthoid diatoms were transferred from Achnanthes or Achnanthidium to new genera based on characteristics observed via scanning electron microscopy (SEM). In this study, we isolated and cultured two Korean freshwater achnanthoid diatoms (Bacillariophyceae), studied their morphological characteristics using SEM, and assessed their molecular characteristics by analysing the nuclear small subunit (SSU) and ribulose-1, 5-bisphosphate carboxylase/oxygenase (rbcL) genes. We emended the description of Lemnicola hungarica with regard to the spindly pore opening of the hymen and the internally convex occlusions of elongated pores on the mantle. In addition, we demonstrated that the valves of L. hungarica are occasionally biseriate to uniseriate towards the valve edge. A morphological comparison of Lemnicola strains and species showed that biseriate rows of areolae are no longer an essential characteristic for allocation to Lemnicola . Based on the SEM and molecular analysis results, we also established a new, small-celled monoraphid species, Lemnicola uniseriata sp. nov., which has elongated areolae occluded by radiately structured hymenes and an elliptic valve shape. The uniseriate areolae of L. uniseriata showed that Lemnicola includes both uniseriate and biseriate striae. Additionally, the results of SSU and rbcL sequence analyses provided strong evidence to support the recognition of L. uniseriata as a new species.